Research on Drilling and Sealing Technology for Cross Bedding of Superthick Coal Seam - Yao-bin Li; Cai-Hao Yue; Xin Guo (Advances in Civil Engineering)
Gas disasters have been affecting coal mine safety production. With the gradual deepening of coal resources development, whether gas extraction meets the standard is particularly important. In view of the low extraction efficiency, through theoretical and numerical simulation combined with field measurement, the upper and lower cross bedding drilling is studied. Through the simulation and comparison of gas pressure at different extraction time and the gas pressure changes when the spacing of boreholes is 8 m, 10 m, and 12 m, the results show that, under the designed parameters, when the pressure value at the middle of the two boreholes starts to be less than 0.74 Mpa, the standard extraction time of the upper and lower cross strata boreholes is 160 days, and the most suitable spacing of boreholes is 10 m. Combined with the actual situation of Baode Mine, the extraction effect of cross drilling and parallel drilling was compared. The research shows that the predrainage effect of cross drilling is obviously better than that of parallel drilling. Cross drilling improves the predrainage effect, prolongs the action time of gas extraction by drilling, and effectively eliminates the risk of coal seam outburst.